EKLIPSE: engaging knowledge holders and networks for evidence-informed European policy on biodiversity and ecosystem services. (10th May 2019) - Watt, Allan; Ainsworth, Gill; Balian, Estelle; Cojocaru, George; Darbi, Marianne; Dicks, Lynn; Eggermont, Hilde; Furman, Eeva; Goudeseune, Lise; Huybrecht, Pierre; Kelemen, Eszter; Koch, Florian; et al.
Abstract : The aim of EKLIPSE is to develop a mechanism to inform European-scale policy on biodiversity and related environmental challenges. This paper considers two fundamental aspects of the decision-support mechanism being developed by EKLIPSE: 1) the engagement of relevant actors from science, policy and society to jointly identify evidence for decision making; and 2) the networking of scientists and other holders of knowledge on biodiversity and other relevant evidence. The mechanism being developed has the potential not only to build communities of knowledge holders but to build informal networks among those with similar interests in evidence, be they those that seek to use evidence or those who are building evidence, or both. EKLIPSE has been successful in linking these people and in contributing to building informal networks of requesters of evidence, and experts of evidence and its synthesis. We have yet to see, however, significant engagement of formal networks of knowledge holders. Future success, however, relies on the continued involvement with and engagement of networks, a high degree of transparency within the processes and a high flexibility of structures to adapt to different requirements that arise with the broad range of requests to and activities of EKLIPSE.